2019
DOI: 10.18004/pdfce/2076-054x/2019.025.49.106-129
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Climate: A look from the Narrative to the Systematization

Abstract: Este es un artículo publicado en acceso abierto bajo una licencia Creative Commons Cardozo. Clima Organizacional....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Willis et al [21] found that a positive perception of organizational climate or stronger identification seemed to cause less stress. Cardozo and Kwan Chung [22] assert that a positive organizational climate can reduce worker stress and fatigue [23], revealing a negative correlation between organizational climate and job stress.…”
Section: The Influence Of Organizational Climate On Job Stressmentioning
confidence: 99%
“…Willis et al [21] found that a positive perception of organizational climate or stronger identification seemed to cause less stress. Cardozo and Kwan Chung [22] assert that a positive organizational climate can reduce worker stress and fatigue [23], revealing a negative correlation between organizational climate and job stress.…”
Section: The Influence Of Organizational Climate On Job Stressmentioning
confidence: 99%
“…Existen estudios sobre el clima organizacional que se basan únicamente en factores externos (autonomía, estructura, recompensas, consideración, cordialidad, apoyo, apertura, entre otras) (García, 2003, Sánchez, et al, 2009 y otros que enfatizan en los factores externos (inversiones, gastos familiares, convivencia familiar, ocio, vida social, etc.) (Cardozo y Kwan Chung, 2019). Por lo tanto, Gonçalves (1997) define al clima organizacional como las condiciones y características del lugar laboral y de las cuales generan percepciones, positivas o negativas, en los colaboradores sobre el estado de su comportamiento.…”
Section: Introductionunclassified
“…En contraste, la cultura organizacional es más resistente al cambio y tiende a ser más estable a lo largo del tiempo. Cambiar la cultura organizacional requiere esfuerzos significativos y sostenidos para alterar los valores y las creencias compartidas, así como para promover nuevas prácticas y comportamientos (Cardozo y Kwan, 2019).…”
unclassified